Intimate violence : anti-Jewish pogroms on the eve of the Holocaust - Kopstein, Jeffrey (Cornell University Press, 2018)
"This book employs archival research and statistical analysis on an original dataset of a summer 1941 wave of anti-Jewish pogroms to show that pogroms occurred not where antisemitism was strongest, but where local Jews challenged local non-Jews' dreams of national dominance"--